Labelling compliance and species identification of herring products sold at large scale retail level within the Italian market. (December 2019) - Tinacci, L.; Guardone, L.; Castro-Palomino Rubio, J.; Riina, M.V.; Stratev, D.; Guidi, A.; Armani, A.
Abstract: The present study aimed at verifying labelling compliance to the current EU legislation, as well as the products' identity against substitution incidents, of processed herring currently available on the Italian market. Totally, one hundred and twenty-two herring samples including whole smoked exemplars, smoked fillets, pickled and canned products were collected. The labels were analyzed against the requirements of Regulation No.1169/2011 and No. 1379/2013 and the product identity was verified by the use of a full and a mini-DNA barcoding protocol. Shortcomings and labelling issue included the absence of a clear allergens highlight in 9.8% of the products analyzed, the incomplete mention to the catching area and the lack of fishing gear declaration in 40% and 33% of the products falling within the scope of Regulation No. 1379/2013. The COI barcodes selected in the study allowed the univocal species identification of all the products which were confirmed belonging to the species Clupea harengus . The substantial labelling compliance and the absence of mislabelling incidents confirmed a high level of food business operators training and control along the herring supply chain and a strong will to protect and enhance the consumers' informed choice. Highlights: 122 variously processed herring samples sold in Italy were analyzed (69). Labels were analyzed against the requirements of Reg. EU 1169/2011 and 1379/2013 (83). Species identity was verified using a full and a mini-DNA barcoding protocol (78). A substantial labelling compliance and absence of mislabelling incidents were found (85). A high level of FBOs' training and awareness along the herring supply chain was shown.